Sensory Analysis Of Starch Garut Utilization (Marantha arundinacea L.) As SubstituteMaterial For Wheat Flour In Making Pasta - Enceng Sobari; Sulton Sabilul Haq (Universitas Darussalam Gontor, 2023)
Substitution food is very important today, it is due to the government's efforts to minimize dependence on imports of raw materials that cannot be provided in Indonesia and have the potential asraw materials that have nutritional content that is close to the original raw materials. The purpose of this study was to determine the influence of arrowroot starch and determine the effect of substitution of arrowroot starch on the level of favorabilityof panelists in starch levels in pasta products. The formulations used are 50% arrowroot starch and 50% wheat flour (P1), 70% arrowroot starch and 30% wheat flour (P2), 100% arrowroot starch and 0% wheat flour (P3). Observations on sensory tests consist of color, aroma, taste, texture, and starch content. Hedonic test data processing using kruskawalis test analysis and Duncan advanced assay. Starch content test data were analyzed using Analysis of Variance (ANOVA) the use of arrowroot starch as a substitution material affects fragrant and texture. Starch levels have decreased due to the processing process. The best treatment in the hedonic test process (color, fragrant, taste, texture) of arrowroot starch paste processing obtained the formulation of adding 50% starch and 50% wheat flour (P1), while in the carbohydrate test, the starch content obtained (67.80%) by the treatment of adding 100% starch and 0% wheat flour (P3).